Opinions of nursing and medical students before the end of their university education on their preparation for work with the dying patient - Mazur , Ewelina; Dobrowolska, Beata; Rabiasz, Renata; Pilewska-Kozak, Anna (Polish Journal of Public Health, 2019)
Introduction. Well-implemented, holistic care of the dying patient requires appropriate qualifications from the medical personnel. Aim. The aim of the study was to collect the opinions of nursing and medical students before the end of their professional education on their preparation to provide care to the dying patient. Material and methods. The survey was carried out in a group of 213 medical and nursing students during their final year of professional education. Results. Students were unable to clearly express their opinion on their preparation to provide care to patients at the end of their lives (87; 40.8%). Nursing students were more likely to perceive themselves as prepared for such care – 30 (26.7%) than medical students – 11 (10.9%). Statistically significant correlation was observed. A large group of the students (92; 43.2%) had never been present at the scene of a patient’s death during clinical classes. The majority of the respondents chose ‘definitely not’ (59; 27.7%) and ‘rather not’ (53; 24.9%) answers when asked if their university education had prepared them for work with patients at the end of their lives. Students considered their knowledge to be lacking mostly in areas such as coping with their own emotions in the face of a patient’s death (137; 64.3%); communicating with a dying person (119; 55.9%); providing care to the patient’s family (154; 72.3%); cooperating with the patient’s family (125; 58.7%). Conclusions. Students of both majors are not certain about the level of their preparation to provide care to people at the end of their lives, nor about the extent to which their university education had introduced them to the specificity of care of a dying patient. The medical students were observed to exhibit higher statistical significance as compared to the nursing students. The university curriculum prepared the students to take care of the dying patient’s biological sphere, but did not prepare them to assume a holistic approach to care of the patient and his family